2013
DOI: 10.1111/aphw.12018
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐Based Tailoring of Behavior‐Change Campaigns: Increasing Fluoride‐Free Water Consumption in Rural Ethiopia with Persuasion

Abstract: Two hundred million people worldwide are at risk of developing dental and skeletal fluorosis due to excessive fluoride uptake from their water. Since medical treatment of the disease is difficult and mostly ineffective, preventing fluoride uptake is crucial. In the Ethiopian Rift Valley, a fluoride-removal community filter was installed. Despite having access to a fluoride filter, the community used the filter sparingly. During a baseline assessment, 173 face-to-face interviews were conducted to identify psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Interestingly, in the present study, perceived vulnerability did not predict habitual cleaning, although perceived severity did. Other studies in the water, sanitation, and hygiene (WASH) domain did not find the latter as a predictor of behavior, neither in a negative nor in a positive association [ Huber et al ., ; Inauen et al ., ; Sonego and Mosler , ]. Hence, the phenomenon needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the present study, perceived vulnerability did not predict habitual cleaning, although perceived severity did. Other studies in the water, sanitation, and hygiene (WASH) domain did not find the latter as a predictor of behavior, neither in a negative nor in a positive association [ Huber et al ., ; Inauen et al ., ; Sonego and Mosler , ]. Hence, the phenomenon needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The model integrates different theories of behavior change and includes a broad set of factors predicting behavior. The approach has successfully been applied to increase safe water consumption in Ethiopia and Bangladesh 10,11 and has moreover proven its effectiveness in increasing handwashing behavior in water-scarce regions in southern Ethiopia. 12 Contextual factors.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing different groups from the same sample, interviewing them with the same instruments, we expect the problem of bias to be equally distributed. Further, it has been shown that successful interventions in changing behavior can be designed on the basis of self-reported behavioral data [15][16][17]61,62]. It might not be relevant after all to measure exact behavior and to validate self-reports about it when we can still explain what factors differentiate between users and non-users of technologies or groups of high and low performers of relevant health behaviors.…”
Section: Discussionmentioning
confidence: 99%